Phytochemical Analysis, Antioxidant Activity and Acute Toxicity Study of Cicerarietinum and Brassica oleracea var. italica - Badoni, Himani; Sharma, Promila; Waheed, S. M.; Singh, Saumya (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968256);" role="presentation">Plants have various bioactive components which are responsible for their different biological <span dir="ltr" style="left: calc(var(–scale-factor)*468.58px); top: calc(var(–scale-factor)*322.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952756);" role="presentation">activities and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*335.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941562);" role="presentation">provides the basis for using plants for treatment of several diseases. The present study involves two different <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895201);" role="presentation">plants <span dir="ltr" style="left: calc(var(–scale-factor)*98.54px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950551);" role="presentation">Cicerarietinum <span dir="ltr" style="left: calc(var(–scale-factor)*162.26px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*179.33px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944476);" role="presentation">Brassica oleracea var. italica, <span dir="ltr" style="left: calc(var(–scale-factor)*303.91px); top: calc(var(–scale-factor)*349.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923758);" role="presentation">locally available in Dehradun, Uttarakhand. Sprouts of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950551);" role="presentation">Cicerarietinum <span dir="ltr" style="left: calc(var(–scale-factor)*137.06px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938351);" role="presentation">and leaves of <span dir="ltr" style="left: calc(var(–scale-factor)*196.73px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975012);" role="presentation">Brassica oleracea var. italica w<span dir="ltr" style="left: calc(var(–scale-factor)*331.03px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">ere <span dir="ltr" style="left: calc(var(–scale-factor)*347.35px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.867765);" role="presentation">washed, <span dir="ltr" style="left: calc(var(–scale-factor)*383.71px); top: calc(var(–scale-factor)*362.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952362);" role="presentation">air dried and then powdered. The <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.854496);" role="presentation">aqueous <span dir="ltr" style="left: calc(var(–scale-factor)*111.72px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*133.42px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918876);" role="presentation">methanolic <span dir="ltr" style="left: calc(var(–scale-factor)*184.75px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89463);" role="presentation">extracts <span dir="ltr" style="left: calc(var(–scale-factor)*222.99px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*238.45px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.841103);" role="presentation">these <span dir="ltr" style="left: calc(var(–scale-factor)*266.03px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898948);" role="presentation">plants <span dir="ltr" style="left: calc(var(–scale-factor)*297.09px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*323.58px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.841067);" role="presentation">used <span dir="ltr" style="left: calc(var(–scale-factor)*349.01px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*367.70px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*387.00px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924511);" role="presentation">phytochemical <span dir="ltr" style="left: calc(var(–scale-factor)*452.94px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.872522);" role="presentation">anaysis. <span dir="ltr" style="left: calc(var(–scale-factor)*491.92px); top: calc(var(–scale-factor)*375.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.877087);" role="presentation">Besides <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904925);" role="presentation">phytochemical assays, <span dir="ltr" style="left: calc(var(–scale-factor)*166.70px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961298);" role="presentation">antioxidant activity of these plants <span dir="ltr" style="left: calc(var(–scale-factor)*313.99px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921937);" role="presentation">were also <span dir="ltr" style="left: calc(var(–scale-factor)*357.31px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.966219);" role="presentation">done. Acute toxicity study was <span dir="ltr" style="left: calc(var(–scale-factor)*490.30px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875545);" role="presentation">done <span dir="ltr" style="left: calc(var(–scale-factor)*513.70px); top: calc(var(–scale-factor)*388.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903412);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*401.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915305);" role="presentation">Wistar rats to determine the toxicity level of these extracts. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*90.26px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923077);" role="presentation">methanolic extract of <span dir="ltr" style="left: calc(var(–scale-factor)*177.77px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950551);" role="presentation">Cicerarietinum <span dir="ltr" style="left: calc(var(–scale-factor)*241.37px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885029);" role="presentation">sprouts <span dir="ltr" style="left: calc(var(–scale-factor)*272.81px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920457);" role="presentation">(CAM) and aqueous extract of <span dir="ltr" style="left: calc(var(–scale-factor)*397.87px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950551);" role="presentation">Cicerarietinum <span dir="ltr" style="left: calc(var(–scale-factor)*461.50px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88198);" role="presentation">sprouts <span dir="ltr" style="left: calc(var(–scale-factor)*492.82px); top: calc(var(–scale-factor)*428.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03242);" role="presentation">(CAA); <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949082);" role="presentation">methanolic extract of <span dir="ltr" style="left: calc(var(–scale-factor)*162.98px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931839);" role="presentation">Brassica oleracea <span dir="ltr" style="left: calc(var(–scale-factor)*240.65px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01377);" role="presentation">var. italica <span dir="ltr" style="left: calc(var(–scale-factor)*289.37px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8635);" role="presentation">leaves <span dir="ltr" style="left: calc(var(–scale-factor)*317.95px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00381);" role="presentation">(BOM) <span dir="ltr" style="left: calc(var(–scale-factor)*351.19px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919572);" role="presentation">aqueous extract of <span dir="ltr" style="left: calc(var(–scale-factor)*430.30px); top: calc(var(–scale-factor)*441.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951485);" role="presentation">Brassica oleracea var. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00109);" role="presentation">italica <span dir="ltr" style="left: calc(var(–scale-factor)*100.82px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900055);" role="presentation">leaves (<span dir="ltr" style="left: calc(var(–scale-factor)*132.26px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00328);" role="presentation">BOM) <span dir="ltr" style="left: calc(var(–scale-factor)*161.66px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900125);" role="presentation">possess various active constituents. <span dir="ltr" style="left: calc(var(–scale-factor)*308.11px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03055);" role="presentation">CAA <span dir="ltr" style="left: calc(var(–scale-factor)*332.35px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940006);" role="presentation">exhibit tannins<span dir="ltr" style="left: calc(var(–scale-factor)*392.23px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899935);" role="presentation">, saponins and <span dir="ltr" style="left: calc(var(–scale-factor)*453.94px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.876983);" role="presentation">pheno<span dir="ltr" style="left: calc(var(–scale-factor)*478.30px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924);" role="presentation">ls, <span dir="ltr" style="left: calc(var(–scale-factor)*490.90px); top: calc(var(–scale-factor)*454.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864258);" role="presentation">whereas <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02345);" role="presentation">CAM <span dir="ltr" style="left: calc(var(–scale-factor)*101.05px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.821278);" role="presentation">possess <span dir="ltr" style="left: calc(var(–scale-factor)*137.42px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896371);" role="presentation">tannins, <span dir="ltr" style="left: calc(var(–scale-factor)*175.07px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879675);" role="presentation">saponins, <span dir="ltr" style="left: calc(var(–scale-factor)*219.05px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929429);" role="presentation">alkaloids, <span dir="ltr" style="left: calc(var(–scale-factor)*264.05px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938927);" role="presentation">flavonoids <span dir="ltr" style="left: calc(var(–scale-factor)*312.67px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*333.43px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887831);" role="presentation">phenols. <span dir="ltr" style="left: calc(var(–scale-factor)*373.27px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00199);" role="presentation">In <span dir="ltr" style="left: calc(var(–scale-factor)*387.89px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89408);" role="presentation">contrast, <span dir="ltr" style="left: calc(var(–scale-factor)*428.50px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0031);" role="presentation">BOA <span dir="ltr" style="left: calc(var(–scale-factor)*455.85px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*476.71px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00302);" role="presentation">BOM <span dir="ltr" style="left: calc(var(–scale-factor)*505.84px); top: calc(var(–scale-factor)*467.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918436);" role="presentation">both <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.913207);" role="presentation">contain<span dir="ltr" style="left: calc(var(–scale-factor)*101.30px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930715);" role="presentation">alkaloids, tannins, <span dir="ltr" style="left: calc(var(–scale-factor)*178.85px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94137);" role="presentation">flavonoids <span dir="ltr" style="left: calc(var(–scale-factor)*224.81px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94098);" role="presentation">and phenols. While <span dir="ltr" style="left: calc(var(–scale-factor)*308.47px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87609);" role="presentation">saponins <span dir="ltr" style="left: calc(var(–scale-factor)*347.11px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">are <span dir="ltr" style="left: calc(var(–scale-factor)*363.07px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869514);" role="presentation">present <span dir="ltr" style="left: calc(var(–scale-factor)*395.71px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974194);" role="presentation">only <span dir="ltr" style="left: calc(var(–scale-factor)*417.22px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01271);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*428.74px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0031);" role="presentation">BOA<span dir="ltr" style="left: calc(var(–scale-factor)*449.74px); top: calc(var(–scale-factor)*481.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950371);" role="presentation">. The TPC results <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907752);" role="presentation">show<span dir="ltr" style="left: calc(var(–scale-factor)*93.02px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.850184);" role="presentation">ed <span dir="ltr" style="left: calc(var(–scale-factor)*106.34px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894722);" role="presentation">that <span dir="ltr" style="left: calc(var(–scale-factor)*125.06px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952338);" role="presentation">BOM (247.79±0.710<span dir="ltr" style="left: calc(var(–scale-factor)*210.65px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992965);" role="presentation">mg GAE g-1) <span dir="ltr" style="left: calc(var(–scale-factor)*268.97px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891463);" role="presentation">has the <span dir="ltr" style="left: calc(var(–scale-factor)*302.11px); top: calc(var(–scale-factor)*494.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974632);" role="presentation">highest phenolic content in it. In TFC analysis, BOA <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885462);" role="presentation">showed <span dir="ltr" style="left: calc(var(–scale-factor)*109.22px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*128.30px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90486);" role="presentation">highe<span dir="ltr" style="left: calc(var(–scale-factor)*150.50px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.853347);" role="presentation">st <span dir="ltr" style="left: calc(var(–scale-factor)*163.82px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94834);" role="presentation">level <span dir="ltr" style="left: calc(var(–scale-factor)*190.08px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*205.13px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941592);" role="presentation">flavonoids <span dir="ltr" style="left: calc(var(–scale-factor)*254.09px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918052);" role="presentation">(104.20±0.10<span dir="ltr" style="left: calc(var(–scale-factor)*307.99px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914679);" role="presentation">mg <span dir="ltr" style="left: calc(var(–scale-factor)*327.41px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922632);" role="presentation">QE g-1). <span dir="ltr" style="left: calc(var(–scale-factor)*370.51px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00199);" role="presentation">In <span dir="ltr" style="left: calc(var(–scale-factor)*385.60px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927223);" role="presentation">DPPH <span dir="ltr" style="left: calc(var(–scale-factor)*417.97px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889067);" role="presentation">scavenging <span dir="ltr" style="left: calc(var(–scale-factor)*469.53px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.858229);" role="presentation">assay, B<span dir="ltr" style="left: calc(var(–scale-factor)*507.22px); top: calc(var(–scale-factor)*507.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00717);" role="presentation">OM (<span dir="ltr" style="left: calc(var(–scale-factor)*75.38px); top: calc(var(–scale-factor)*520.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925027);" role="presentation">87.22±0.011<span dir="ltr" style="left: calc(var(–scale-factor)*125.90px); top: calc(var(–scale-factor)*520.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965708);" role="presentation">) showed maximum % inhibition. <span dir="ltr" style="left: calc(var(–scale-factor)*267.41px); top: calc(var(–scale-factor)*520.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969894);" role="presentation">After acute toxicity study <span dir="ltr" style="left: calc(var(–scale-factor)*375.55px); top: calc(var(–scale-factor)*520.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936242);" role="presentation">plant extracts were found to be safe <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*534.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906489);" role="presentation">even at highest concentration of 2000 mg kg-1